Regioselective Synthesis of Some Pyrazole Scaffolds Attached to Benzothiazole and Benzimidazole Moieties - Nabila A. Kheder; Yahia N. Mabkhot; Fawzia R. Zahian; Sara S. Mohamed (Journal of Chemistry)
Condensation of 2-(benzothiazol-2-yl)acetonitrile (1) or 2-(1-methyl-1H-benzimidazol-2-yl)acetonitrile (2) with thiophene-2-carbaldehyde afforded the corresponding acrylonitrile derivatives 3 or 4, respectively. The 1,3-dipolar cycloaddition reaction of the acrylonitrile 3 or 4 with nitrile-imine 6 gave novel pyrazole derivatives pendant to benzothiazole and benzimidazole. The pyrazoline derivative 7 was converted into the corresponding pyrazole derivative 11 via thermal elimination of hydrogen cyanide upon heating in sodium ethoxide solution. The structures of the synthesized products were confirmed by IR, 1H NMR, and mass spectral techniques.